Integrated Management of Corynespora cassiicola (Berk. and Curt.) Wei. Causal Agent of Target Spot Disease in Cotton - Prasad, B. M. V. S.; Bhattiprolu, S. L.; Kumar, V. M.; Jayalalitha, K.; Kumar, D. V. S. R. (International Journal of Bio-resource and Stress Management, 2025)
Laboratory experiments were conducted during during kharif (July 2019–February 2020 and July 2020–February 2021) in the Department of Plant Pathology, Agricultural College, Bapatla and field experiments with selected treatments were carried out at Regional Agricultural Research Station (RARS), Lam, Guntur, Andhra Pradesh to develop an integrated management strategy against Corynespora leaf spot of cotton. Evaluation of fungicides, biocontrol agents, salicylic acid, potash and phosphate salts revealed that carbendazim, carbendazim+mancozeb and propiconazole at 250, 500, 750 and 1000 ppm and salicylic acid at 5.0 and 6.5mM completely inhibited the mycelial growth of cotton isolate of Corynespora cassiicola. Both phosphorous acid (79.98%) and ammonium dihydrogen phosphate (48.72%) showed reduction of mycelial radial growth in poisoned food technique. Trichoderma isolate T 18001 grew fast and exhibited deformation, demelanization, protoplast aggregation and finally lysis of mycelia in dual cultures. Pseudomonas fluorescens (PF1), Bacillus subtilis BS2, Actinomycetes (ACT2) were found to be effective with 39.23, 40.26 and 41.03% inhibition, respectively, as against control (3.90 cm) and induced shrinkage of Corynespora mycelia, reduction of interseptal length, demelanization in mycelia, excessive production of chlamydospores and finally, hyphal lysis at the zone of interaction. Propiconazole at 0.1% resulted in the lowest per cent disease index (12.4), highest yield (2931.7 kg ha-1) and BC ratio of 1.46 followed by carbendazim+mancozeb at 0.1% (13.9 PDI, 2851.1 kg ha-1 and 1.42) and were significantly superior to other treatments as against control (27.3 PDI, 2265.6 kg ha-1 and 1.13), respectively.